Vitamin D analogue TX 527 down-regulates the NF-κB pathway and controls the proliferation of endothelial cells transformed by Kaposi sarcoma herpesvirus - González Pardo, María Verónica (2013)
Background and Purpose: The Kaposi sarcoma (KS)-associated herpesvirus GPCR (vGPCR) is a key molecule in the pathogenesis of KS, where it increases NF-κB gene expression and activates the NF-κB pathway. We investigated whether the less calcemic vitamin D analogue TX 527 inhibited the proliferation of endothelial cells transformed by vGPCR by modulation of the NF-κB pathway. Experimental Approach: Endothelial cells transformed by vGPCR (SVEC-vGPCR) were treated with TX 527. Proliferation was measured by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl) -2H-tetrazolium, inner salt (MTS) and cell cycle by flow cytometry. mRNA and protein levels were measured by real-time quantitative reverse transcriptase-PCR (qRT-PCR) and immunoblot analysis respectively. Key Results: TX 527, similar to bortezomib (0.5 nM), a proteasome inhibitor that inhibits the activation of NF-κB, reduced proliferation and induced G0/G1 cell cycle arrest in SVEC-vGPCR. TX 527 like 1α,25(OH)2D3, biological active form of vitamin D, decreased the activity of NF-κB comparable with the effect of bortezomib. Time-response studies showed that TX 527 significantly decreased NF-κB and increased IκBα mRNA and protein levels. The increase of IκBα was accompanied by a reduction in p65/NF-κB translocation to the nucleus. These responses were abolished when vitamin D receptor (VDR) expression was suppressed by stable transfection of shRNA against VDR. In parallel with NF-κB inhibition, there was a down-regulation of inflammatory genes such as IL-6, CCL2/MCP and CCL20/MIP3α. Conclusions and Implications: These results suggest that the anti-proliferative effects of the vitamin D analogue TX 527 in SVEC-vGPCR occur by modulation of the NF-κB pathway and are VDR dependent.